2008
DOI: 10.1080/13613320802110217
|View full text |Cite
|
Sign up to set email alerts
|

“I don't think I'm a racist”: Critical Race Theory, teacher attitudes, and structural racism

Abstract: 2008) "I don't think I'm a racist": Critical Race Theory, teacher attitudes, and structural racism, Race Ethnicity and Education, 11:2, 95-113,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(101 citation statements)
references
References 24 publications
2
99
0
Order By: Relevance
“…The first, and largest, explores race and power, especially with respect to whiteness and urban education (Marx, 2006;Pennington, 2007;Vaught & Castagno, 2008). These studies by and large examine how White privilege affects the assumptions and the knowledge teachers construct about their students' abilities, behavior, or potential.…”
Section: Perspective 4: Identitymentioning
confidence: 99%
“…The first, and largest, explores race and power, especially with respect to whiteness and urban education (Marx, 2006;Pennington, 2007;Vaught & Castagno, 2008). These studies by and large examine how White privilege affects the assumptions and the knowledge teachers construct about their students' abilities, behavior, or potential.…”
Section: Perspective 4: Identitymentioning
confidence: 99%
“…Indeed, through participation in these courses, students seemed to develop an understanding of a direct but implicit link between previous experiences with racial diversity and 'goodness' or non-racist-ness. Similarly, Kailin (1999) and Vaught and Castagno (2008) both found that some practicing teachers equated teaching students of colour as an assertion of anti-racism. Participants in the present study who had attended racially diverse high schools engaged in a parallel leap by claiming that their previous experiences with racially diverse peers automatically denoted a non-racist perspective.…”
Section: Theme 1: Participants Voiced Appreciation For Racial Diversimentioning
confidence: 99%
“…Teachers already hold a position of power over their students due to the hierarchy of the educational system. Yet based on their membership in the dominant group, white teachers may have additional cultural power over their students of color since whiteness and racism are entrenched in our schools (Vaught & Castagno, 2008). Along with the systemic racism in schools white teachers have had life-long support of their beliefs related to people of color, yet by developing "cultural competence and socio-political consciousness" teachers can become better educators (Picower, 2009, p. 199).…”
Section: Review Of the Literaturementioning
confidence: 99%